Is there an overlapping market between national car producers in Malaysia? - Hayder Abbas Drebee; Nor Azam Abdul Razak; Mohd Zaini Abd Karim (Penerbit Universiti Kebangsaan Malaysia, 2014)
This paper examines how the choice of three broad categories of automobiles in Malaysia (i.e. Proton, Perodua, and foreign automobiles) is affected by a change in the price of a specific car model. Using a sample of 478 automobile owners in Malaysia, a discrete choice analysis is conducted based on the conditional logit model. In general, it is found that the own-price effect on Proton (Perodua) cars is negatively related to a specific Proton (Perodua) model; in contrast, the cross-price effect on Proton (Perodua) cars is positively related to a specific Perodua (Proton) model. Of the nine models evaluated, three of them show a significant overlapping market segment. This finding implies that Proton and Perodua should differentiate these products further to lessen competition between them.